On following pages: 36. Nelson's Collared Lemming (Dicrostonyx nelsoni); 37. Ogilvie Mountains Collared Lemming (Dicrostonyx nunatakensis); 38. Richardson's Collared Lemming (Dicrostonyx richardsoni); 39. Palearctic Collared Lemming (Dicrostonyx torquatus); 40. Unalaska Collared Lemming (Dicrostonyx unalascensis); 41. Gray Red-backed Vole (Craseomys rufocanus); 42. Hokkaido Red-backed Vole (Craseomys rex); 43. Korean Red-backed Vole (Craseomys regulus); 44. Shanxi Red-backed Vole (Craseomys shanseius); 45. ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (The Canadian Field-Naturalist, 2017)
On following pages: 36. Nelson's Collared Lemming (Dicrostonyx nelsoni); 37. Ogilvie Mountains Collared Lemming (Dicrostonyx nunatakensis); 38. Richardson's Collared Lemming (Dicrostonyx richardsoni); 39. Palearctic Collared Lemming (Dicrostonyx torquatus); 40. Unalaska Collared Lemming (Dicrostonyx unalascensis); 41. Gray Red-backed Vole (Craseomys rufocanus); 42. Hokkaido Red-backed Vole (Craseomys rex); 43. Korean Red-backed Vole (Craseomys regulus); 44. Shanxi Red-backed Vole (Craseomys shanseius); 45. Anderson's Red-backed Vole (Craseomys anderson); 46. Smith's Red-backed Vole (Craseomys smithii); 47. Western Red-backed Vole (Myodes californicus); 48. Southern Red-backed Vole (Myodes gapperi); 49. Bank Vole (Myodes glareolus); 50. Tian Shan Red-backed Vole (Myodes centralis); 51. Large-eared Vole (Myodes macrotis); 52. Northern Red-backed Vole (Myodes rutilus); 53. Silver Mountain Vole (Alticola argentatus); 54. White-tailed Mountain Vole (Alticola albicauda); 55. Kashmir Mountain Vole (Alticola ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 297, DOI: 10.5281/zenodo.6707142 ...